Are plants the new oil? Responsible innovation, biorefining and multipurpose agriculture. (November 2015) - Shortall, O.K.; Raman, Sujatha; Millar, Kate
Abstract: Bioenergy is seen as one of the options for industrialised countries to wean themselves off fossil fuels. However bioenergy, transport biofuels in particular, has faced considerable environmental and social controversies. Biorefining has been proposed in the UK and Denmark to address these concerns by using biomass efficiently for multiple purposes (food, feed, fuel, chemicals). Drawing from frameworks on responsible innovation, this paper opens up the implicit assumptions within the biorefinery concept about how biomass should be produced. Stakeholder interviews show that the biorefinery concept is framed within an industrial agricultural paradigm that aims to overcome controversies through large-scale production stimulated by biotechnology innovation. By contrast, an "alternative agriculture" paradigm envisions sustainable multipurpose biomass production in terms of on-farm nutrient and energy cycling and local, smaller scale production. However, there is a potential overlap through the concept of quality industrial biomass production. These three visions provide different perspectives on the bioeconomy in terms of the differences between biomass and fossil fuels; and where biomass should come from. Policy development for bioenergy must reckon with these different visions in innovation pathways for multipurpose biomass. Highlights: The biorefinery is seen as a way for bioenergy to overcome resource constraints. Interviews were carried out with stakeholders in UK and Danish bioenergy sectors. Industrial and alternative agriculture visions of biomass production were found. An overlapping vision of quality biomass production was also found. Policy should remain aware of and potentially support different innovation pathways.